Are "classical" tests of repeated-sprint ability in football externally valid? A new approach to determine in-game sprinting behaviour in elite football players. Issue 6 (18th March 2016) - Schimpchen, Jan; Skorski, Sabrina; Nopp, Stephan; Meyer, Tim
ABSTRACT: The aim of this study was to investigate the occurrence of repeated sprinting bouts in elite football. Furthermore, the construct validity of current tests assessing repeated-sprint ability (RSA) was analysed using information of sprinting sequences as they actually occurred during match-play. Sprinting behaviour in official competition was analysed for 19 games of the German national team between August 2012 and June 2014. A sprinting threshold was individually calculated based on the peak velocity reached during in-game sprinting. Players performed 17.2 ± 3.9 sprints per game and during the entire 19 games a total of 35 bouts of repeated sprinting (a minimum of three consecutive sprints with a recovery duration <30 s separating efforts). This averages one bout of repeated sprinting per player every 463 min. No general decrement in maximal sprinting speed was observed during bouts with up to five consecutive sprints. Results of the present study question the importance of RSA as it is classically defined. They indicate that shorter accelerations are more important in game-specific situations which do not reach speeds necessary to qualify them as sprints. The construct validity of classic tests of RSA in football is not supported by these observations.